2014
DOI: 10.1159/000368747
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oral Factor Xa Inhibitors after Acute Coronary Syndrome

Abstract: Despite an early invasive strategy and the use of dual antiplatelet therapy, patients with acute coronary syndrome (ACS) continue to be at substantial risk for recurrent ischemic events. It is believed that this risk is, at least in part, due to an intrinsic coagulation pathway that remains activated for a prolonged period after ACS. Earlier studies using warfarin showed a reduction in ischemic events, but the overall benefits were offset by increased bleeding complications. Recently, there has been increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Two factors (factor Xa and thrombin -factor II a) are involved in the process of clot formation. The thrombin production persists beyond acute presentation, and, consequently, antithrombin therapy, in addition to platelet inhibition, has been proposed [65][66][67]. Warfarin plus aspirin reduce the risk of ischaemic events after ACS with or without stenting when compared to aspirin alone.…”
Section: Areas Of Uncertainty Concerning Dat or Tat Regimens Post Procedures And Post Dischargementioning
confidence: 99%
“…Two factors (factor Xa and thrombin -factor II a) are involved in the process of clot formation. The thrombin production persists beyond acute presentation, and, consequently, antithrombin therapy, in addition to platelet inhibition, has been proposed [65][66][67]. Warfarin plus aspirin reduce the risk of ischaemic events after ACS with or without stenting when compared to aspirin alone.…”
Section: Areas Of Uncertainty Concerning Dat or Tat Regimens Post Procedures And Post Dischargementioning
confidence: 99%
“…Apixaban also proved to be unprofitable in trials APPRAISE (Apixaban for Prevention of Acute Ischemic Events) and APPRAISE-2 and it has also been demonstrated that the concomitant use of anti-platelet drugs with these agents increases risk without benefit. ATLAS ACS 2-TIMI 46 and 52 investigated reduced doses of rivaroxaban and revealed its association with lower ischemic and bleeding risks, as well as a decrease in both stent thrombosis and mortality rates; therefore suggesting rivaroxaban to be a potential choice for anticoagulation in triple therapy in the future [68,[70][71][72].…”
Section: Stroke Prevention In Acute Coronary Syndromementioning
confidence: 99%
“…Several recent studies have demonstrated the importance of factor Xa as a promising anticoagulant target, in addition to, the usage of many factor Xa inhibitors to prevent and treat a lot of thrombotic diseases [1][2][3][4][5][6] . The coagulation process involves proteins in coagulation reactions, which are called blood coagulation factors.…”
Section: Introductionmentioning
confidence: 99%